FINANCIAL PERFORMANCE OF CULINARY MSMEs IN JEBRES DISTRICT, SURAKARTA CITY BASED ON FINANCIAL LITERACY, FINANCIAL INCLUSION, AND FINANCIAL TECHNOLOGY - Edi Wibowo; Berliana Christian Widayat (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
The financial well-being of micro, small, and medium enterprises (MSMEs) plays a vital role in driving economic growth and fostering entrepreneurship in urban areas. In this context, the culinary sector in Jebres District, Surakarta City, has emerged as a significant contributor to the local economy. However, the performance and sustainability of these culinary MSMEs depend on various factors, including their level of financial literacy, access to financial services, and utilization of financial technology. Understanding the influence of these factors on the financial performance of culinary MSMEs is crucial for devising effective strategies to support and enhance their economic impact. This study aims to determine and analyze the significance of the influence of financial literacy, financial inclusion, and financial technology on the financial performance of culinary micro, small, and medium enterprises (MSMEs) in Jebres District, Surakarta City. The research method employed in this study is a survey conducted among culinary MSMEs in Surakarta City, utilizing quantitative data. The findings indicate that financial literacy has a significant effect on the performance of culinary MSMEs in Jebres District, Surakarta City, which has been proven. Similarly, financial inclusion has also been proven to have a significant impact on the performance of culinary MSMEs in Jebres District, Surakarta City. Additionally, it has been established that financial technology significantly affects the financial performance of culinary MSMEs in Jebres District, Surakarta City.